2022
DOI: 10.1155/2022/4146742
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise with Mediterranean-DASH Intervention for Neurodegenerative Delay Diet Promotes Brain Cells’ Longevity despite Sex Hormone Deficiency in Postmenopausal Women: A Randomized Controlled Trial

Abstract: Objective. To investigate the combined impact of aerobic exercise and Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet on brain cells longevity in spite of sex hormones deficiency in obese postmenopausal women. Design. A parallel randomized clinical trial. Subjects/Patients. Sixty-eight eligible postmenopausal women were randomly assigned to one of two groups, one experimental and one control. The participants’ age ranged from 60 to 75 years, and their body mass index ranged from 30 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Six-weeks of aerobic exercise and laughter therapy resulted in a significant increase in 6-MWTD, FIM, and MMSE scores (p <0.001) when compared to aerobic exercise alone (p <0.001), as noticed in this study, which is consistent with Dos Anjos et al (29) , who reported a significant impact of moderate intensity aerobic exercise on functional capacity in diabetic elderly (p <0.001), and Elsayed et al (30) results, which showed a significant effect of aerobic exercise on functional and cognitive level in elderly women (p <0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Six-weeks of aerobic exercise and laughter therapy resulted in a significant increase in 6-MWTD, FIM, and MMSE scores (p <0.001) when compared to aerobic exercise alone (p <0.001), as noticed in this study, which is consistent with Dos Anjos et al (29) , who reported a significant impact of moderate intensity aerobic exercise on functional capacity in diabetic elderly (p <0.001), and Elsayed et al (30) results, which showed a significant effect of aerobic exercise on functional and cognitive level in elderly women (p <0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Of 57,721 unique records, 109 articles of 54 studies were included in the evidence map as they provided information on outcomes assessed (Figure 1 and Table S4). 34–87 The unique accession numbers from all database searches are available upon request.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity and sarcopenic obesity (SO) in older adults are major public health issues, due to their increasing prevalence. 1,2 Obesity prevalence among older adults (60 years and older) ranges from 20.9% in Europe to 43.3% in the United States. [3][4][5] The prevalence of SO is difficult to establish due to the different definitions and cutoffs applied.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve of the studies were conducted in Iran, 39–41 , 49 , 53 , 54 , 57–59 , 61–63 one of which was an RCT. 40 The rest of the studies spanned across Egypt, 65 China, 42 , 51 , 64 the United States 48 , 55 , 56 , 60 and Australia. 47 , 50 , 52 …”
Section: Resultsmentioning
confidence: 99%